Preliminary biometrical analysis on three similar hippuritid species - Caffau, Mauro; Pleničar, Mario (Geologija, 1994)
The hippuritids species Hippuritella lapeirousei (Goldfuss, 1840), Hippuritella nabresinensis (Futterer, 1893) and Hippuritella heritschi (Kühn, 1947) were studied through biometrical analysis. For this purpose, the areas of three morphological characters which are related by their biological functions (as described by Realy, 1992) were measured on transversal sections of lower valves. These morphometrical values are: a) Shell area (Sa), b) inner area (Ia) and c) pillars area (Pl-P2a). This analysis highlighted a morphological similarity between Hl. nabresinensis and Hl. heritschi, meanwhile the morphometric values for Hl. lapeirousei showed to be different.